CCD-PHOTOMETRY OF RV TAU-TYPE STARS - Burnasheva, B. A.; Burnasheva, B. A. (Одеські астрономічні публікації, 2017)
On the figure 1 there are the result of the wavelet-analysis of the common data of the visual and photograpic photometry of the variables. Besides of the nearly cyclic variations of the duration of the primary RV Tau-type cycle, there are also chaotic variations of the cycle too.